2021
DOI: 10.1016/j.jbc.2021.101393
|View full text |Cite
|
Sign up to set email alerts
|

ALG-2 and peflin regulate COPII targeting and secretion in response to calcium signaling

Abstract: ER-to-Golgi transport is the first step in the constitutive secretory pathway, which, unlike regulated secretion, is believed to proceed nonstop independent of Ca 2+ flux. However, here we demonstrate that penta-EF hand (PEF) proteins ALG-2 and peflin constitute a hetero-bifunctional COPII regulator that responds to Ca 2+ signaling by adopting one of several distinct activity states. Functionally, these states can adjust the rate of ER export of COPII-sorted cargos… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
36
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(41 citation statements)
references
References 42 publications
5
36
0
Order By: Relevance
“…The reason for the opposite effect of peflin depletion in Sargeant et al . 39 and McGourty et al . 40 is not known.…”
Section: Calcium and Secretionmentioning
confidence: 92%
See 4 more Smart Citations
“…The reason for the opposite effect of peflin depletion in Sargeant et al . 39 and McGourty et al . 40 is not known.…”
Section: Calcium and Secretionmentioning
confidence: 92%
“…Other cellular studies showed that recombinant ALG-2 bound to Sec31 was able to stabilize ERES 31 , 36 , and dominant-negative ALG-2 37 and depletion 38 studies also indicated a positive regulatory role. Recently, our lab helped reconcile some of these apparent contradictions by demonstrating that ALG-2 can either stimulate or inhibit ER-to-Golgi transport in the same system 39 . This duality in the regulatory role of ALG-2 may come down to multiple partners it can bind under different circumstances.…”
Section: Calcium and Secretionmentioning
confidence: 99%
See 3 more Smart Citations